Why Don’t More Mitochondrial Diseases Exhibit Cardiomyopathy? - Nina Singh; Mindong Ren; Colin K. L. Phoon (Journal of Cardiovascular Development and Disease, 2023)
Background: Although the heart requires abundant energy, only 20–40% of children with mitochondrial diseases have cardiomyopathies. Methods: We looked for differences in genes underlying mitochondrial diseases that do versus do not cause cardiomyopathy using the comprehensive Mitochondrial Disease Genes Compendium. Mining additional online resources, we further investigated possible energy deficits caused by non-oxidative phosphorylation (OXPHOS) genes associated with cardiomyopathy, probed the number of amino acids and protein interactors as surrogates for OXPHOS protein cardiac “importance”, and identified mouse models for mitochondrial genes. Results: A total of 107/241 (44%) mitochondrial genes was associated with cardiomyopathy; the highest proportion were OXPHOS genes (46%). OXPHOS (p = 0.001) and fatty acid oxidation (p = 0.009) defects were significantly associated with cardiomyopathy. Notably, 39/58 (67%) non-OXPHOS genes associated with cardiomyopathy were linked to defects in aerobic respiration. Larger OXPHOS proteins were associated with cardiomyopathy (p < 0.05). Mouse models exhibiting cardiomyopathy were found for 52/241 mitochondrial genes, shedding additional insights into biological mechanisms. Conclusions: While energy generation is strongly associated with cardiomyopathy in mitochondrial diseases, many energy generation defects are not linked to cardiomyopathy. The inconsistent link between mitochondrial disease and cardiomyopathy is likely to be multifactorial and includes tissue-specific expression, incomplete clinical data, and genetic background differences.